Standardized Shiga-Toxin Encoding Genes Real-Time PCR Screening Methods Comparison and Development of an Internally Controlled Assay for Pan-stx2 Detection. (16th March 2021) - Hu, Ying; Bai, Li; Zhao, Linna; Wu, Lingling; Lv, Hong; Li, Qiongqiong; Li, Xinpeng; Xie, Qingchao; Wang, Lili; Liu, Chengwei; Liu, Na; Cui, Shenghui
Abstract: Background: Various primer and probe sets have been developed and standardized, but certain sets may have low efficiency or miss some stx -subtypes. Objective: To compare the efficiency of the recommended stx screening primers and probe sets in four standardized methods and develop a new primers and probe system with an internal amplification control (IAC) for all known stx2 subtypes. Method: The inclusivity and specificity of recommended screening primers and probe sets in four standardized methods were compared. A new pan- stx2 primer and probe set was adapted from the International Organization for Standardization (ISO) method for all known stx2 subtypes. The robustness of the new method was assessed in seven laboratories and also assessed in ground beef and bean sprout samples. Results: None of the recommended screening primers and probe sets in the four standardized methods could efficiently amplify all the stx2 subtypes because of various mismatches in the primers or the probe sequences. A new primers and probe system adapted from the ISO method, through introducing degenerate bases in primers and probe sequences with an IAC, showed high amplification efficiency and specificity for all known stx2 subtypes in ground beef and bean sprouts samples. The specificity of the new method was assessed in seven laboratories and showed robust and consistent results. Conclusions: This study provided evidence for Shiga-toxin producing Escherichia coli (STEC) screening method development, and the newly developed primers and probes system should be considered in the revision of the standardized methods. Highlights: None of the recommended screening primer and probe set in the four official methods could efficiently amplify all the stx2 subtypes. A new developed primer and probe set showed high amplification efficiency and specificity for all known stx2 subtypes in fresh ground beef and bean sprouts samples. The newly developed stx2 screening system showed robustness and consistency during interlaboratory study.